Effect of hydromechanical stress on cellular antigens of Bordetella pertussis - Rodríguez, María Eugenia (1996)
Cells of Bordetella pertussis grown in a bioreactor under stirring conditions were studied to investigate the effect of shear stress on cellular-bound filamentous haemagglutinin (FHA). FHA attached to the bacterial surface, unlike extracellular FHA, was not affected at the shear levels tested. Moreover, no other cellular immunogen involved in the whole-cell protective activity seemed to be affected by hydromechanical forces.